SCHOOL EXAMINATION METHODS AND STUDENTS’ PERFORMANCES IN NIGERIA (COMPUTERAND PAPER BASED EXAMINATION IN FOCUS) - Kehinde Abimbola ADIGUN, Mumuni Idowu ADARABIOYO, Samuel Olawseun ADEJUWON,Oluwaseyi Adesina ADEYEMO,Bayowa Teniola BABALOLA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This work compares students’ academic performances in examinations in Nigeria using computer based examination (CBE) and paper based examination (PBE). The data for this work was gathered with the aid of questionnaire form Federal University of Technology Akure (FUTA) which is structured to examine the view of students about certain factors that influences their performances based on the type of examination. Multiple regression and Analysis of Variance (ANOVA) were used to analyze the data and the results revealed that students can maximize their time and attempt more question on Paper Based Examination than Computer Based Examination. It was also revealed that students read better when preparing to write Paper Based Examination than Computer Based Examination, since the computer based examinationsare mostly objectives. Again,in Paper Based Examination, Lecturers covers more curriculum than Computer Based Examination.It is recommended that students should be giving more training on how to use Computer before giving themComputer Based Examinationand it will help them to perform better in their academic performances.